Pola Konsumsi Makanan Pada Ibu Hamil Yang Mengalami Kurang Energi Kronis (Kek) Di Wilayah Kerja Puskesmas Cakranegara Kota Mataram - Ni Putu Anita Candri; Susilo Wirawan; I Nyoman Adiyasa; Aladhiana Cahyaningrum (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Maternal dietary consumption patterns include the frequency, type and the amount of food consumed by pregnant women. Based on research Rahmaniar (2011) maternal food consumption patterns associated with the incidence of chronic energy deficiency. The Basic Health Research 2010 shows pregnant women who consume energy and protein below the minimum of national requirements, respectively 44.8% and 49.5%. Objective. The aim of this study is to describe the pattern of food consumption in pregnant women who experience chronic energy deficiency in Puskesmas Cakranegara Mataram City 2015.  The design of the study conducted by descriptive observational and total sample are 26 pregnant women who suffered chronic energy deficiency. Research Methods. Data were collected include the characteristic of the sample in which most of the samples have a lifespan in the range of 20-35 years, with a junior high school education level and the age of pregnancy is in the second trimester. Research Result. Maternal dietary consumption patterns show that the type of food source of energy and a common builder are consumed by pregnant women who suffered chronic energy deficiency is rice, bread, dried noodles, biscuits, chicken, pindang, eggs, tofu and tempeh. As for the food source of energy and protein are often consumed is rice, biscuits, pindang, eggs, chicken and tempeh. The level of energy, protein, fat and carbohydrate consumption of chronic energy feficiency pregnant women are mostly located in the deficit category. Conclusion. The pattern of food consumption of pregnant women who suffered chronic energy deficiency which often consume are rice, biscuits, pindang, eggs and tempeh as well as the level of energy and macro nutrients consumption that are in deficit category.